Effects of high hydrostatic pressure on physicochemical and functional properties of walnut (Juglans regia L.) protein isolate. (30th August 2012) - Qin, Zihan; Guo, Xingfeng; Lin, Yan; Chen, Jiluan; Liao, Xiaojun; Hu, Xiaosong; Wu, Jihong
Abstract BACKGROUND: Walnut (Juglans regia L.) is a good source of protein that has potential application in new product formation and fortification. The main objectives of this study were to investigate the effects of high hydrostatic pressure (HHP) treatment (300–600 MPa 20 min) on physicochemical and functional properties of walnut protein isolate (WPI) using various analytical techniques at room temperature. RESULTS: The results showed significant modification of solubility, free sulfhydryl content and surface hydrophobicity with increased levels of HHP treatment, indicating partial denaturation and aggregation of proteins. Differential scanning calorimetry and fluorescence spectrum analyses demonstrated that HHP treatment resulted in gradual unfolding of protein structure. Emulsifying activity index was significantly (P < 0.05) increased after HHP treatment at 400 MPa, but significantly decreased (P < 0.05) relative to the untreated WPI with further increase in pressure. HHP treatment at 300–600 MPa significantly decreased emulsion stability index. Additionally, HHP‐treated walnut proteins showed better foaming properties and in vitro digestibility. CONCLUSION: These results suggest that HHP treatment could be applied to modify the properties of walnut proteins by appropriate of pressure levels, which will help in using walnut protein as a potential food ingredient. © 2012 Society of Chemical Industry